MANAJEMEN KURIKULUM PADA KELAS AKSELERASI - Rakhmawati, Indah Fadliyyah (AS-SALAM, 2017)
Every human being has different abilities. There are those who have potential in certain fields and not necessarily able in other fields. Some have intelligence (intelligence question) above average and some are IQ below average. But basically there is no stupid child, only the child whose IQ is below the average is rather slow in achieving an educational goal. While the child whose IQ is being he will continue to follow the learning process in accordance with the targeted curriculum. For children whose IQ is above average, they will learn more quickly in the education process. In children who have above average ability, need to be treated proportionally. With the potential development of children with above-average capabilities, they do not have to wait for other children to achieve schooling. They can get education in a fast time. Then there is the need for a class for children who have the ability to exceed children of his age. One solution to the problem with the holding of acceleration classes. For children who have special intelligence it is necessary for the development of learning. For that we need a curriculum. Curriculum serves as a tool to achieve the goal, which is able to deliver students through teaching and learning activities undertaken by teachers to students to become human beings in accordance with the goals of education naisonal. Curriculum can be done with the curriculum management so that the curriculum used in acceleration classes can be organized and adjusted to the conditions of students in acceleration classes so that the goal of education is achieved. Keywords: Curriculum Management, Acceleration Class